Development of a Nanoparticle-Based Oral Vaccine for Atlantic Salmon Against Isav Using an Alphavirus Replicon as Adjuvant - Spencer-Ossa, E; Sandino-Garcia, A; Rivas-Aravena, A; Brito-Ramírez, T (Academic Press, 2015)
Adjuvants used in vaccine aquaculture are frequently harmful for the fish, causing melanosis, granulomas and kidney damage. Along with that, vaccines are mostly administered by injection, causing pain and stress to the fish. We used the DNA coding for the replicase of alphavirus as adjuvant (Ad) of a vaccine against ISAV. The Ad and an inactivated ISAV (V) were loaded in chitosan nanoparticles (NPs) to be administered orally to Atlantic salmon. NP-Ad was able to deliver the DNA ex vivo and in vivo. Oral administration of the NPs stimulated the expression of immune molecules, but did not stimulate the humoral response. Although the vaccination with NP-V results in a modest protection of fish against ISAV, NP-V administered together with NP-Ad caused a protection of 77%. Therefore, the DNA coding for the replicase of alphavirus could be administered orally and can potentiate the immuneprotection of a virine against infection. © 2015 Elsevier Ltd.